A Research Paper About Influence of Social Media in Agriculture Marketing With Reference to India - Kulkarni, Aaditi Sanjay (Indian Journal of Computer Science, 2020)
Conventionally newspapers, television, and magazines have controlled agricultural information interchange. Since the introduction of social media, communication is transforming into a new dynamic every day. Platforms like Facebook and WhatsApp have 346.2 million [10] and 400 million [11], active users, as of 2020. Communication has become virtual more than physical. People, young or adult, remain influenced by social media and it is a trend that is not going down very soon. Despite all the advantages, its exact use in rural areas of developing countries is still low due to infrastructural difficulties and psychological barriers. Skill and proficiency in using social media are lacking. The survey on the use of social media in agricultural marketing conducted using a questionnaire, 103 respondents provided fascinating results. WhatsApp was found to be the most popular social media platform used by participants. The principal source of information for the participants was determined to be in contact with farmers. A majority of participants admitted that infrastructure, lack of technical knowledge, and lack of understanding of working on social media are some of the challenges in adopting social media. Most of the participants also acknowledged that there is a need for training and creating awareness to popularize the practice of social media. The current pandemic has created innovative opportunities for use of social media in agriculture marketing. Overall, we can state that social media plays an influential role in agriculture marketing.